Espaços De Lipschiz-Livres E Propriedades De Aproximação - Romao, Joao Victor Bateli [UNIFESP] (2018)
This Work Consists Of Studying Approximation Properties In Lipschitz-Free Spaces, Which Involves: In-Depth Study Of Prerequisites Of Functional Analisys And Topology In Order To Comprehend The Engaged Concepts; Research And Analisys Of Existant Bibliography On The Subject; And The Detailed Study Of Specific Results In This Area, Prioritizing Recent Central Results Under The Development Of The Area.